Towards the Description and Representation of Smartness in IoT Scenarios Specification - de Souza, Bruno Pedraça; Motta, Rebeca Campos; Travassos, Guilherme Horta (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
Contemporary Software Systems (CSS) embraces the Internet of Things (IoT) paradigm. Such a paradigm has allowed new technologies, and it is leading to more autonomous and smarter software systems in the fourth industrial revolution. The demand for CSS has grown considerably, highlighting new challenges in their engineering to assure final quality. The lack of adequate software technologies to support the capturing of specific features, such as their smartness capacity, represents one of the challenges faced by software engineers in CSS. This work raises the discussions towards capturing and representing smartness regarding IoT software systems. Therefore, it investigates the use of a scenario-based requirements specification technique to support dealing with smartness in IoT software systems. The results of an observational study indicate that IoT scenarios could capture the smartness characteristics of the system, although, some previous experience in IoT can lead to better results, which suggests the need to more training of software engineers to deal with smartness in IoT software systems.